Tungsten-doped MoS2-based nanostructure for photocatalytic hydrogen evolution under visible light - Ahmad, Khursheed; Raza, Waseem; Khan, Mohd Quasim; Khan, Rais Ahmad (Reaction Kinetics Mechanisms and Catalysis, 2024)
In this work, we introduced a simple approach to boost the photocatalytic activity of MoS2 by introducing transition metal (W) doping. The W-MoS2 (10 mg) exhibited a substantial enhancement in photocatalytic activity for H2 production, achieving an impressive rate of approximately 925 µmol g−1 after 6 h, which is 1.5-fold higher than bare MoS2. The highest H2 production activity of 1740 µmol g−1 after 6 h was obtained for 50 mg W-MoS2 photocatalyst. The observed increase in activity can be ascribed to the formation of a Schottky barrier at the heterojunction interface, along with advantageous properties of improved active sites resulting from tungsten doping into MoS2. Furthermore, the enhanced activity of W-MoS2 may be attributed to the promotion of catalytic kinetics by tungsten and molybdenum sites, exhibiting commendable activity for water dissociation and higher efficiency in H+ adsorption. These factors contribute significantly to the overall improved performance of the W-MoS2 photocatalyst. Further, platinum (Pt) was also used as cocatalyst and enhanced photocatalytic activity of 2145 µmol g−1 after 6 h was observed for W-MoS2 + 5 wt% Pt.
CRIS-Team Scopus Importer:2024-05-10
Keywords: Hydrogen evolution; Photocatalytic system; Tungsten doped MoS